The development of mathematical HOTS questions based on banten culture - Anis Yuliani; Fitri Alfarisa; Tiurlina Tiurlina (SAINTIS Publishing, 2022)
The resulted of a survey conducted by the Organization for Economic Cooperation and Develop-ment based on the 2018 Program for International Student Assessment were obtained from 78 countries, Indonesian students ranked 72nd in math ability. The reason is that the 2013 curricu-lum that has been implemented in Indonesia is eurocentric. The transformation sought in the field of education is the improvement of high order thinking skills and mathematical abilities. Educa-tion and culture cannot be separated from regular daily life because culture covers all aspects of life while education is a primary need for everyone. This study used the Research and Develop-ment (RD) method with the Martin Tessmer (1993) model, which is formative research. The validity of the values obtained above 0.80 means that the questions are valid. The level of practi-cality of the questions obtained is 96.25%, very practical category. The reliability coefficient of 0.891, reliable. The level of difficulty is known to be 80% of the items in the medium category, 20% of the items in the difficult category. The discriminatory power of the question is known to all items (100%) in good category, meaning that good questions are used to classify the level of stu-dents thinking abilities.